2017
DOI: 10.14393/bj-v33n4a2017-36559
|View full text |Cite
|
Sign up to set email alerts
|

Leaf anatomy and gas exchange of ornamental sunflower in response to silicon application

Abstract: Silicon applied to substrate for greenhouse cultivation of ornamental pot plants can improve the yield and quality of the ornamental product; however, the possible anatomical and physiological changes caused by Si have to be assessed. Therefore, the objective of this study was to evaluate gas exchange rates and leaf anatomy of ornamental sunflower 'Sunbright' grown on a substrate amended with Si. The experiment was conducted in a greenhouse, and the treatments consisted of sunflower plants cultivated in pots c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Higher DMYS may be due to an increased photosynthetic activity and a lower rate of transpiration, both enhanced by Si (ZANÃO JÚNIOR et al, 2017), although not evaluated here, which probably contributed to the increase of this variable. The presence of Si also promotes lignification and suberization of the root tissue (FLECK et al, 2011), which may explain the higher DMYR observed in plants grown with Si.…”
Section: Contentmentioning
confidence: 76%
“…Higher DMYS may be due to an increased photosynthetic activity and a lower rate of transpiration, both enhanced by Si (ZANÃO JÚNIOR et al, 2017), although not evaluated here, which probably contributed to the increase of this variable. The presence of Si also promotes lignification and suberization of the root tissue (FLECK et al, 2011), which may explain the higher DMYR observed in plants grown with Si.…”
Section: Contentmentioning
confidence: 76%
“…The most abundant trichomes with shortest size-NGTs-were found on adaxial side of leaves in AuSi-NPs treatment (Table 3). Silica was most likely integrated and accumulated directly to the basal part of leaf trichomes with phytolites formation [61]. In general, elemental silica does not belong to essential nutrients, but several works pointed to its higher plant-tolerant function against abiotic and biotic stress [61], ability to reduce accumulation of reactive oxygen species (ROS), membrane lipid peroxidation, access inhibition to toxicants, and enhanced plant defense to pathogens [62].…”
Section: Changes Of Leaf Surface Structures-trichomes and Stomata Aft...mentioning
confidence: 99%
“…Ma & Yamaji (2016) adds that plants where there is a rich source of Si, have greater tolerance to toxic metals such as Aluminum (Al), Manganese (Mn) and Iron (Fe) and heavy Cadmium (Cd) and Lead (Pb) and gains in quality and productivity in agricultural crops. Carvalho et al (2009) and Zanão Júnior et al (2017) further discusses that Si considerably influences sunflower plants grown in pots for floristic or experimental interest where they report gains in production and quality of flowering and seed production.…”
Section: Introductionmentioning
confidence: 99%